Synthesis, Anthelmintic, Insecticidal Activity of (E)-1-((1-(6-Chlorobenzo[d]thiazol-2-yl)-3-phenyl-1H-pyrazol-4-yl)methylene)-2-(6-substituted benzo[d]thiazol- 2-yl)hydrazine Derivatives - Himaja, M.; Munirajasekhar, D.; Karigar, Asif; Ramana, M.V.; Sikarwar, Mukesh (Asian Journal of Chemistry, 2012)
A new series of (E)-1-((1-(6-chlorobenzo[d]thiazol-2-yl)-3-phenyl-1H-pyrazol-4-yl)methylene)- 2-(6-substitutedbenzo[d]thiazol-2-yl)hydrazine derivatives (6a-6e) were synthesized and the structure of all the compounds was confirmed by IR, 1H NMR and mass spectral analysis. All the newly synthesized compounds were evaluated for anthelmintic activity against earthworm species (Eudrilus eugeniae and Megascolex konkanensis) and the insecticidal activity was carried out against termites (Coptotermis formasanus) using chloropyrifos as the standard drug.